Sex differences in the peripheral levels of cytokines during 12-month antipsychotic treatment in a drug-naïve schizophrenia spectrum cohort - I. Ratke; A. Torsvik; C.A. Bartz-Johannessen; F. Fathian; I. Joa; S.M. Klæbo Reitan; E.M. Løberg; M. Rettenbacher; S. Skrede; V.M. Steen; E. Johnsen; R.A. Kroken (Brain, Behavior, & Immunity - Health)
Background: There are substantial sex differences in schizophrenia. However, research addressing sex differences regarding the antipsychotic effect on the immune system is lacking. The aim of our study was to compare changes in cytokine levels in men and women with schizophrenia spectrum disorder over 12 months of treatment with antipsychotics. Methods: This study reports pre-planned secondary outcomes from the BeSt InTro Study – a pragmatic, semi-randomised, rater-blinded comparison of amisulpride, aripiprazole, and olanzapine. The groups were analysed collectively. Of the 144 enrolled patients with schizophrenia spectrum disorders and ongoing psychosis, 56 were antipsychotic-naïve at baseline (20 women and 36 men) and were included in this study. Blood samples from these 56 patients were drawn at baseline, prior to treatment with antipsychotics, and 1, 3, 6, 12, 26, 39, and 52 weeks after initiation of antipsychotic medication. Duration of treatment was 52 weeks. Serum cytokine levels were assessed with a multiplex immunoassay. Changes in the levels of IL-4, IL-6, TNF-α, IL-1β, IL-2, IL-10, IL-12p70, IL-17A, IFN-γ and CRP from baseline to the different follow-up times were analysed using linear mixed effects models separately for men and women, and then compared. Outcomes: Cytokine levels were mainly stable in men during the study period. In women, IL-4 levels were lower at baseline compared with men (p = 0.048) and showed a consistent and significant increase at weeks 6 (p = 0.006), 26 (p < 0.001), 39 (p = 0.002), and 52 (p = 0.001). TNF-α increased in women at weeks 26 (p = 0.008) and 39 (p = 0.012). IL-6 had a transient increase in women at weeks 12 (p = 0.003) and 26 (p = 0.007). There were significant sex differences in progression of cytokine levels at weeks 3 (IL-6: p = 0.046), 6 (IL-4: p = 0.022, IL-6: p = 0.015), 12 (IL-6: p = 0.01), 26 (IL-4: p < 0.001, IL-6: p = 0.015, TNF-α: p = 0.026), 39 (IL-4: p = 0.003, TNF-α: p = 0.023) and 52 (IL-4: p < 0.001, TNF-α: p = 0.009). CRP levels did not differ between sexes at baseline or during the study period and did not change significantly during treatment with antipsychotics in either sex. Interpretation: We found significant sex differences in serum cytokine changes in drug-naïve patients with schizophrenia during treatment with antipsychotics. Cytokine levels were mainly altered in women, with increased IL-4, IL-6, and TNF-α levels. Cytokine changes may dramatically affect mental as well as somatic health. Our findings add to already established sex differences in schizophrenia pathophysiology and might have a potential role for future treatment guidelines. Funding: The Research Council of Norway, the Western Norway Regional Health Trust, and the participating hospitals and universities provided funding for this study.